Penggembalaan sebagai Manifestasi Agape dalam Pemenuhan Kasih kepada Kristus: Kajian Teologis St. Yohanes Krisostomos - Hendi Hendi (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This article explores the concept of pastoral ministry as the highest expression of agape (divine love) in St. John Chrysostom's work, On the Priesthood. Unlike interpretations that tend to view pastoral ministry as a managerial function, Chrysostom emphasizes the ontological and eschatological dimensions of the priestly vocation. This study comprehensively analyzes Chrysostom's key arguments linking the willingness to shepherd Christ's flock with the pinnacle of love for Him, and how the responsibility of the priesthood demands moral and spiritual qualities that surpass individual virtue. The article argues that Chrysostom not only presents a pastoral ideal but also offers a sharp critique of formalism and ambition in ecclesiastical leadership, which remains relevant today. Thus, this research is expected to provide new insights into the enduring relevance of Chrysostom's thought in forming spiritual leadership grounded in true agape.